Analisis Hubungan Techno-Overload terhadap Kelelahan Emosional dan Kinerja Karyawan: Tinjauan Literatur Review - Yahya, Aulia; Suminar, Dewi Retno (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The adaptation of technology by organizations often leads to techno-overload, a situation where technology forces users to work faster and longer, resulting in decreased performance and increased stress. This research aims to identify the relationship between techno-overload to performance, and emotional exhaustion of employees through the theoretical basis of definitions and findings from several experts. The method used was a systematic literature review following the stages of identification, screening, eligibility, and inclusion. Articles were collected from the Scopus database. From this process, 15 selected articles were analyzed in depth to explore the relationship between techno-overload, performance, and emotional exhaustion. The results showed that techno-overload, a situation where individuals feel overwhelmed by the technology they have to use, can lead to emotional exhaustion. Individuals who experience emotional exhaustion tend to feel physically and emotionally drained, thus unable to give their best in their work. In addition, emotional exhaustion also reduces employees' motivation and ability to contribute to their full potential, which ultimately results in decreased performance and difficulty in maintaining concentration. This research indicates that organizations need to manage techno-overload well to reduce its negative impact on emotional exhaustion and improve employee performance.